2019
DOI: 10.1080/00131881.2019.1642121
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality and equity in schools in socially disadvantaged areas

Abstract: Background: Recent effectiveness studies have investigated the relationship between two dimensions of effectivenessnamely, quality and equity. Specifically, the question of whether effective schools can also reduce the initial differences in student outcomes attributed to student background factors has been examined. In this context, the Dynamic Approach to School Improvement (DASI) makes use of theory and the research findings of effectiveness studies to try to improve school effectiveness in terms of quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Finally, it is noted that the socio-demographic characteristics of students in the surveyed schools also predict student achievement. An important aspect of low SES is confirmed by the insights of other researchers that high SES students consistently outperform low SES students (Kyriakides et al, 2019;Xuan et al, 2019) and that girls are more engaged in learning than boys (Kessels & Houtte, 2021;Lam et al, 2016). Researchers name the reasons for explaining low SES student achievement: from neuronal development (Rosen et al, 2018) to mindset differences (Destin et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, it is noted that the socio-demographic characteristics of students in the surveyed schools also predict student achievement. An important aspect of low SES is confirmed by the insights of other researchers that high SES students consistently outperform low SES students (Kyriakides et al, 2019;Xuan et al, 2019) and that girls are more engaged in learning than boys (Kessels & Houtte, 2021;Lam et al, 2016). Researchers name the reasons for explaining low SES student achievement: from neuronal development (Rosen et al, 2018) to mindset differences (Destin et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…According to the researchers (Kyriakides et al, 2019;Schmidt et al, 2015), low SES students have lower learning engagement and academic achievement compared to high SES students. These results are associated with certain characteristics of low SES students, such as health, food, and mindset (Jensen, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also assessment criteria, which are influenced by promotion rates and will be skewed towards subject performance in junior schools. As primary schools have great potential to promote excellence in education, schools should not adopt a universal criterion for evaluating teaching staff but should rate them according to the characteristics of their teaching at different stages [23,24].…”
Section: Problems With Teaching Managementmentioning
confidence: 99%
“…In a recent study conducted by DeVries et al (2018) , students’ achievement was predicted by family SES level as better grades in math and reading were directly related to parental education. Kyriakides et al (2019) examined the effects of SES gap on students’ achievement in mathematics and language courses and showed that effective teaching techniques and classroom practices can fill SES gap. These results also highlighted the importance of mediators on SES roles in a given society.…”
Section: Introductionmentioning
confidence: 99%